2014
DOI: 10.4162/nrp.2014.8.4.352
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of methanol extract fromErigeron CanadensisL. may be involved with upregulation of heme oxygenase-1 expression and suppression of NFκB and MAPKs activation in macrophages

Abstract: BACKGROUND/OBJECTIVESIn this study, we determined the anti-inflammatory activities and the underlying molecular mechanisms of the methanol extract from Erigeron Canadensis L. (ECM) in LPS-stimulated RAW264.7 macrophage cells.MATERIALS/METHODSThe potential anti-inflammatory properties of ECM were investigated by using RAW264.7 macrophages. We used western blot assays and real time quantitative polymerase chain reaction to detect protein and mRNA expression, respectively. Luciferase assays were performed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…In fact, inhibition of NF-κB p65 activation LPS-induced was achieved through SP treatment indicating an anti-inflammatory effect of SP. Accordingly, other authors found that anti-inflammatory effects on RAW 264.7 of the molecules are exerted through NF-κB suppression [38]. NF-κB is also directly involved in pro-inflammatory responses such as adhesion and migration of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, inhibition of NF-κB p65 activation LPS-induced was achieved through SP treatment indicating an anti-inflammatory effect of SP. Accordingly, other authors found that anti-inflammatory effects on RAW 264.7 of the molecules are exerted through NF-κB suppression [38]. NF-κB is also directly involved in pro-inflammatory responses such as adhesion and migration of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LPS acts as an inducer of lung injury and it is used to establish a model of ALI [1,36]. In an experimental murine model of ALI, LPS caused damage to endothelial and epithelial barriers and activated neutrophils and macrophages, thereby releasing various pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6 [37][38][39]. It has been reported that these pro-inflammatory cytokines activate and recruit neutrophils to cross the vascular endothelium into the lung and cause a cascading inflammatory response to amplify tissue injury [11,13,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EA11 also upregulates the expression of PPAR- γ , another recognized anti-inflammatory mediator [ 19 , 20 ] ( Figure 3(c) ). Several natural products have been demonstrated the induction of HO-1 expression in macrophages and thus eliminate the expression of proinflammatory mediators [ 21 , 22 ]. EA11 has added another into this natural product list.…”
Section: Discussionmentioning
confidence: 99%